Design of Tree-Frog-Inspired Adhesives. (15th May 2020) - Langowski, Julian K A; Dodou, Dimitra; van Assenbergh, Peter; van Leeuwen, Johan L
Synopsis: The adhesive toe pads of tree frogs have inspired the design of various so-called 'smooth' synthetic adhesives for wet environments. However, these adhesives do not reach the attachment performance of their biological models in terms of contact formation, maintenance of attachment, and detachment. In tree frogs, attachment is facilitated by an interconnected ensemble of superficial and internal morphological components, which together form a functional unit. To help bridging the gap between biological and bioinspired adhesives, in this review, we (1) provide an overview of the functional components of tree frog toe pads, (2) investigate which of these components (and attachment mechanisms implemented therein) have already been transferred into synthetic adhesives, and (3) highlight functional analogies between existing synthetic adhesives and tree frogs regarding the fundamental mechanisms of attachment. We found that most existing tree-frog-inspired adhesives mimic the micropatterned surface of the ventral epidermis of frog pads. Geometrical and material properties differ between these synthetic adhesives and their biological model, which indicates similarity in appearance rather than function. Important internal functional components such as fiber-reinforcement and muscle fibers for attachment control have not been considered in the design of tree-frog-inspired adhesives. Experimental work on tree-frog-inspired adhesives suggests that the micropatterning of adhesives with low-aspect-ratio pillars enables crack arresting and the drainage of interstitial liquids, which both facilitate the generation of van der Waals forces. Our analysis of experimental work on tree-frog-inspired adhesives indicates that interstitial liquids such as the mucus secreted by tree frogs play a role in detachment. Based on these findings, we provide suggestions for the future design of biomimetic adhesives. Specifically, we propose to implement internal fiber-reinforcements inspired by the fibrous structures in frog pads to create mechanically reinforced soft adhesives for high-load applications. Contractile components may stimulate the design of actuated synthetic adhesives with fine-tunable control of attachment strength. An integrative approach is needed for the design of tree-frog-inspired adhesives that are functionally analogous with their biological paradigm.